(untitled) (TSUL LEGAL REPORT, 2026)
This article provides a practical analysis of the evaluation, legal examination and monitoring of investment projects, the requirements for investment projects, the content and legal aspects of investment projects based on applicable law and the mechanism of their operation. The scope of reforms implemented by the Republic of Uzbekistan to improve the investment climate is also discussed. In addition, this article highlights the urgency of introducing a new mechanism for monitoring investment projects, as well as fully emphasizes the importance of monitoring investment projects to ensure the stability of the national economy.